Development Opportunities of Health, Wellness and Sports Services in Medical Tourism Based on a Research Study - Müller, Anetta; Pfau, Christa; Gabnai, Zoltán; Bácsné Bába, Éva; Borbély, Attila; Pető, Károly (International Journal of Engineering and Management Sciences, 2018)
The quality and quantity of additional services play an increasing role in the competitiveness of service providers in the tourism sector. In our research, our goal was to explore the service development possibilites of two different sites of a Northern Hungarian healthcare institution in the framework of a market research. In the field of services, we focused on different issues of health, wellness and sports services. Our research has shown that the availability of additional services and therapeutic recreational, sport or wellness services are important for patients as they can positively influence their quality of life and health status.